Sediment Depositional History and Processes for the Eurasian Basin Since 54 Ma, Arctic Ocean - Pingchuan Tan; Chunyang Wang; Fei Wang; Jiabiao Li (Geochemistry, Geophysics, Geosystems)
Abstract The Eurasian Basin in the Arctic Ocean, comprising the Amundsen and Nansen Basins separated by the Gakkel Ridge, has sediment deposits up to 4–5 km thick. However, its sedimentation history and processes remain poorly understood. Using 31 seismic profiles, we have estimated deposition rates for 54 Ma. From 54 to 45 Ma, the Nansen Basin averaged ∼15 cm/kyr, while the Amundsen Basin exhibited higher but variable rates (15–50 cm/kyr). From 45 to 20 Ma, the Amundsen Basin's rates decreased significantly, dropping to 6–7 cm/kyr (34–45 Ma) and ∼3.5 cm/kyr (20–34 Ma). Meanwhile, the Nansen Basin maintained higher rates (∼12 cm/kyr to ∼5 cm/kyr). After 20 Ma, sedimentation rates diverged further. The Nansen Basin stabilized at ∼5 cm/kyr and was significantly influenced by glaciation and iceberg rafting, while the Amundsen Basin continued to decline to ∼2 cm/kyr, with pelagic sediments dominated by sea‐ice and iceberg rafting, and debris flows near the Lomonosov Ridge. The Nansen Basin's higher rates are likely due to its proximity to the Barents and Laptev Sea shelves, while the general declined rates across the basin are related to basin expansion, climate cooling, and reduced tectonic activity. Additionally, the Eurasian Basin's sedimentation is shaped by two phases of Siberian river activity. Before 45 Ma, the Lena and Indigirka rivers dominated, particularly near the eastern Laptev Sea Shelf. After 45 Ma, the Pyasina and Yenisey rivers became the main contributors, with significant sediment delivery through the St. Anna Trough. Sediment deposits (0.6–1 km) along the Gakkel Ridge (70°E−100°E) are also caused by these processes.